L’humain et l’écran, à l’écran : The Cat, the Reverend and the Slave d’Alain Della Negra et Kaori Kinoshita (2010) - Anaïs Guilet (Sillages Critiques)
The Cat, the Reverend and the Slave is a documentary directed by Alain Della Negra and Kaori Kinoshita (2010). It portrays three users of Second Life and offers an unprecedented view on an interfaced, mediated way of life. In the film, the cinema screen opens on the connected screen in a staging symbolizing this interface. The screen is the place where users of Second Life and spectators alike can observe how interactions with the technical device (the avatar) but also with others, materialize. If the body is not obsolete yet, the documentary manages to alternate online and offline perspectives. It offers a tragicomic view of these dual beings, these distributed-selves and questions how digital technology reconfigures our modes of presence to ourselves, to others, and to the world. The film literally re-incarnates these avatars, which are both traces of a presence to oneself as well as a tool enabling communication. The connected screen seems to be so in more ways than one since it appears in the film as a vector of social linking.